KEKERASAN DALAM PENDIDIKAN - Eka Hendry (AT-TURATS, 2016)
Education and violence are two contradictory aspects ideally, because education leads a person to becoming better and wiser while violence tends to reduce the human value (dehumanization). However, in real life, violence is always practiced in the education context. Teachers (including parents) often violate their students' right with their utterance, behaviour and action. Sometimes, they are not aware of the violence they have done. This article explores the root of violence practices in education. Such as teacher's mindset of violence and education as well as regulation related to education. To overcome these problems, the writer recommends some strategies be practiced to reduce the violence in education.